2018
DOI: 10.1002/1873-3468.13209
|View full text |Cite
|
Sign up to set email alerts
|

Solution structures of the SH3 domains from Shank scaffold proteins and their interactions with Cav1.3 calcium channels

Abstract: Shank proteins are abundant scaffold proteins in the postsynaptic density (PSD) region of brain synapses. Mutations in Shank proteins are associated with autism, schizophrenia, and Alzheimer's disease. To gain insights into Shank protein interactions at the PSD, we determined the solution structures of the src homology 3 (SH3) domains of all three mammalian Shank proteins. Our findings indicate that they have identical and typical SH3 folding motifs, but unusual target-binding pockets. An investigation into th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 55 publications
0
4
1
Order By: Relevance
“…In contrast to some prior reports, our data provided no indication that the Shank3 SH3 domain plays a significant role in this interaction (Zhang et al, 2005). The reasons for this discrepancy are unclear, but it is possible that a low affinity interaction of CaV1.3L with the SH3 domain (e.g., Ishida et al, 2018) could not be detected under our experimental conditions. These in vitro studies also indicated that β auxiliary subunits had a hitherto unappreciated role in facilitating Shank3 interactions with CaV1.3L LTCCs, apparently by also interacting with Shank3.…”
Section: The Shank3 Pdz Domain Mediates Basal Cav13 Clustering In Int...contrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to some prior reports, our data provided no indication that the Shank3 SH3 domain plays a significant role in this interaction (Zhang et al, 2005). The reasons for this discrepancy are unclear, but it is possible that a low affinity interaction of CaV1.3L with the SH3 domain (e.g., Ishida et al, 2018) could not be detected under our experimental conditions. These in vitro studies also indicated that β auxiliary subunits had a hitherto unappreciated role in facilitating Shank3 interactions with CaV1.3L LTCCs, apparently by also interacting with Shank3.…”
Section: The Shank3 Pdz Domain Mediates Basal Cav13 Clustering In Int...contrasting
confidence: 99%
“…Prior studies indicate that the Shank3 PDZ and SH3 domains interact directly with the C terminal-ITTL motif of Ca V 1.3 L and an adjacent proline-rich region, respectively (Perfitt et al, 2020; Zhang et al, 2005). However, structural studies indicated that the Shank3 SH3 domain is atypical and has only weak (or no) interaction with multiple Ca V 1.3-based proline-rich peptides (Ishida et al, 2018; Ponna et al, 2017). In addition, an N-terminal extension to the Shank3 PDZ domain is critical for high-affinity interactions with GKAP (Zhou et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to a prior report (Zhang et al, 2005), our data provided no indication that the Shank3 SH3 domain plays a significant role in this interaction. The reasons for this discrepancy are unclear, but it is possible that a low affinity interaction of Ca V 1.3 L with the SH3 domain (Ishida et al, 2018) could not be detected under our experimental conditions. These in vitro studies also indicated that β auxiliary subunits had a hitherto unappreciated role in facilitating Shank3 interactions with Ca V 1.3 L LTCCs, apparently by also interacting with Shank3.…”
Section: Discussionmentioning
confidence: 74%
“…Prior studies indicate that the Shank3 PDZ and SH3 domains interact directly with the C terminal‐ITTL motif of Ca V 1.3 L and an adjacent proline‐rich region, respectively (Perfitt et al, 2020; Zhang et al, 2005). However, structural studies indicated that the Shank3 SH3 domain is atypical and has only weak (or no) interaction with multiple Ca V 1.3‐based proline‐rich peptides (Ishida et al, 2018; Ponna et al, 2017). In addition, an N‐terminal extension to the Shank3 PDZ domain is critical for high‐affinity interactions with GKAP (Zhou et al, 2016), but its role in binding Ca V 1.3 is poorly understood.…”
Section: Resultsmentioning
confidence: 99%
“…The Lymnaea stagnalis neuron model has also shown that such interaction is required for synaptic activity (Spafford, Chen, Feng, Smit, & Zamponi, 2003). In contrast, the corresponding C-terminal region of Ca V 2.1 is not an essential determinant for its subcellular localization even the PDZ binding motif is also conserved in the long variant of Ca V 2.1 (Hu, Saegusa, Hayashi, & Tanabe, 2005 (Hu et al, 2005). Studies in vitro introduced the concept of presynaptic "slots" to refer to presynaptic binding sites that are specific for channels to regulate their participation in neurotransmission.…”
Section: Ca 2+ /Calmodulin-dependent Serine Protein Kinase (Cask) Tmentioning
confidence: 99%